Tidally driven ice speed variation at Helheim Glacier, Greenland, observed with terrestrial radar interferometry. Issue 226 (2015) - Voytenko, Denis; Stern, Alon; Holland, David M.; Dixon, Timothy H.; Christianson, Knut; Walker, Ryan T.
Abstract: We used a terrestrial radar interferometer (TRI) at Helheim Glacier, Greenland, in August 2013, to study the effects of tidal forcing on the terminal zone of this tidewater glacier. During our study period, the glacier velocity was up to 25 m d –1 . Our measurements show that the glacier moves out of phase with the semi-diurnal tides and the densely packed melange in the fjord. Here detrended glacier displacement lags behind the forecasted tidal height by ∼8 hours. The transition in phase lag between the glacier and the melange happens within a narrow (∼500 m) zone in the fjord in front of the ice cliff. The TRI data also suggest that the impact of tidal forcing decreases rapidly up-glacier of the terminus. A flowline model suggests this pattern of velocity perturbation is consistent with weak ice flowing over a weakly nonlinear bed.